Breaking the taboo: An exploration of female university students' experiences of attending a feminist‐informed sex education course - Askew, Julie (Sex Education : Sexuality, Society and Learning, 2007)
This article presents the results of a qualitative interview study of nine young women who attended a feminist-informed human sexuality course as undergraduate students at a US university located in the "Bible belt". The course focused on messages of desire and empowerment, rather than romance or fear, and was designed to encourage students to think critically about current sexual discourses. Results indicate that participants' information on sexual issues prior to taking the course was limited and largely negative. Experiences of the course are described in themes including owning sexual desire, improved body image, reduced guilt and fear, and increased confidence as a woman. It is concluded that sex education may be used to help empower female students and enrich their quality of life; current educational practices should therefore be examined for ways in which they are oppressive to development.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; discipline; image corporelle; jeunes femmes*; pédagogie; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle; états-unis; étude qualitative

Fonction sexuelle masculine et sexualité féminine - Giami, Alain (Communications, 2007)
Major changes have occurred in male and female sexual function/dysfunction research and treatments. Male erectile dysfunction has been re-conceptualized as an organic dysfunction, which marks a dramatic shift from previous conceptions of psychogenic impotence developed during the 60' and the 70's. This shift is based on major scientific discoveries, and pharmacological advances that took place since the early 80's under the influence of North American urologists. The release of sildenafil in 1998 was thecorner stone of a new paradigm of treatments focusing on male penile activity, far remote from any psychological approaches. More recently, the same group of urologists started to reconsider Female Sexual Dysfunction using the same organic/biological model of sexual function. New pharmaceutical products are currently under trial for the treatment of this new category of female sexual disorder. But as opposed to the absence of public adverse reaction to the development of this approach of male function, many voices raised to oppose this new conception of female function. A major discussion took place in the British Medical Journal (2003) stating that female sexual function was not organically driven, but rather determined by the social, psychological and interpersonal context of female sexual activity and relations. One of the major dimension of this discussion opposed the so-called "simplicity" of male sexual function to the "complexity" of female sexual function.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; essentialisme; europe; féminisme radical; patriarcat; premier cycle; pédagogie; périodes historiques; recherche; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

Les enjeux de la suppression hormonale des menstruations : une analyse des discours de professionnels de la santé - Nader, Mélissa (Université du Québec à Montréal, 2007)
Le débat sur la suppression des menstruations, présent dans les années 1950, reprend aujourd’hui de la vigueur, en raison de la mise en marché récente de contraceptifs visant l’espacement ou l’interruption des règles. La présente recherche poursuit trois objectifs : dresser le portrait des positions adoptées par les professionnels de la santé au Québec à l’égard de la suppression des menstruations, analyser les discours sur cette pratique à l’aide des perspectives féministes radicale, individualiste et essentialiste, et évaluer dans quelle mesure cette pratique s’inscrit dans le concept de médicalisation du corps des femmes.
Keywords: 2000 à aujourd'hui; 2000-2009; IREF; discipline; menstruations; mémoires/thèses; périodes historiques; santé; santé des femmes*; sciences humaines; sociologie; thématiques